2015
DOI: 10.3892/mmr.2015.3765
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the proliferation, cytotoxic activity and cytokine secretion function of cascade primed immune cells and cytokine-induced killer cells in vitro

Abstract: The present study aimed to compare the antitumor effects of cascade primed immune (CAPRI) cells and cytokine-induced killer (CIK) cells in vitro, through investigating cell morphology, proliferation, cytotoxic activity to tumor cells and the ability of these cells to secrete cytokines. Peripheral blood samples (50 ml) were obtained from three healthy volunteers and peripheral blood mononuclear cells (PBMCs) were obtained from each via Ficoll-Conray density gradient centrifugation. Each suspension of PBMCs (1×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The onset of cells maturation, cluster-like formation, could be observed on day 7, while fully matured suspended CIK clusters could be observed on day 14. This goes with the results reported by Li et al [45], who cultured MNCs for 14 days and found that the cells began to proliferate within 3 days and became fully matured as colonies in suspension within 14 days. On the other hand, these findings were not in line with Bonanno et al [46], Niam et al [31], and Wei et al [38], who cultured human PBMCs for 21, 28, and 15 days, respectively, to reach the maturation stage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The onset of cells maturation, cluster-like formation, could be observed on day 7, while fully matured suspended CIK clusters could be observed on day 14. This goes with the results reported by Li et al [45], who cultured MNCs for 14 days and found that the cells began to proliferate within 3 days and became fully matured as colonies in suspension within 14 days. On the other hand, these findings were not in line with Bonanno et al [46], Niam et al [31], and Wei et al [38], who cultured human PBMCs for 21, 28, and 15 days, respectively, to reach the maturation stage.…”
Section: Discussionsupporting
confidence: 91%
“…The CIK cells' cytotoxic effect on cancerous cells showed variable degrees of efficacy in several tumors including malignant lymphoma either Hodgkin's disease or non-Hodgkin's lymphoma [49], hematological malignancies as acute myeloid and acute lymphocytic leukemia [50] and chronic lymphocytic leukemia [51]. Recent in vitro studies had further shown the potential activity of CIK cells differentiated from the blood of healthy or patient volunteers against breast cancer [30], pancreatic cancer [52], sarcomas [53], ovarian cancer [44], metastatic melanoma [54], glioblastoma or brain cancer [55], solid tumors [45], and gallbladder cancer [56]. In this study, the cytotoxic effect of CIK cells was investigated on HCC in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine-induced killer cell-based therapy provides an immunotherapeutic approach involving anti-tumor effects via direct cell-cell-contact-mediated apoptosis and secretion of cytokines (118). To further boost the effects of cytokineinduced killer cells, the approach may be combined with tumor-specific dendritic cells presenting tumor antigens and orchestrating T-cell response.…”
Section: Gastric Cancer and Adenocarcinoma Of The Gastroesophageal Jumentioning
confidence: 99%
“…Compared with other immune cells, CIK cells have greater proliferative capability, broader anti-tumor spectrum and stronger anti-tumor ability [ 3 , 9 ]. CIK cells’ tumoricidal ability relies on inducing tumor cell apoptosis through direct contact and secretion of cytokines such as IL-2, TNF-a and IFN-γ [ 10 ], and the cytotoxicity of CIK cells is not affected by immune inhibitors such as CsA and FK506 [ 11 ]. Dendritic cells (DC) are the most potent antigen-presenting cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%